2012
DOI: 10.1073/pnas.1109261108
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic spreading of Bacillus subtilis biofilms driven by an extracellular matrix

Abstract: Bacterial biofilms are organized communities of cells living in association with surfaces. The hallmark of biofilm formation is the secretion of a polymeric matrix rich in sugars and proteins in the extracellular space. In Bacillus subtilis, secretion of the exopolysaccharide (EPS) component of the extracellular matrix is genetically coupled to the inhibition of flagella-mediated motility. The onset of this switch results in slow expansion of the biofilm on a substrate. Different strains have radically differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
346
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(376 citation statements)
references
References 32 publications
28
346
0
2
Order By: Relevance
“…Bacteria are known to selforganize into multicellular communities, commonly known as biofilms, in which microbial cells live in close association with a solid surface or liquid-air interface and are embedded in a self-produced extracellular matrix. Extracellular polymeric substances (EPSs) play an important role in determining the structural and mechanical architecture of a biofilm (7)(8)(9)(10)(11)(12). Generally, the collective dynamics of bacterial colony involves a complex interplay of various physical, chemical, and biological mechanisms, such as growth and differentiation of cells, production of EPSs, the collective movement of cells determined by interacting physical forces and chemical cues, e.g., chemotaxis, motility, cellcell signaling, adhesion, and gene regulation (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Bacteria are known to selforganize into multicellular communities, commonly known as biofilms, in which microbial cells live in close association with a solid surface or liquid-air interface and are embedded in a self-produced extracellular matrix. Extracellular polymeric substances (EPSs) play an important role in determining the structural and mechanical architecture of a biofilm (7)(8)(9)(10)(11)(12). Generally, the collective dynamics of bacterial colony involves a complex interplay of various physical, chemical, and biological mechanisms, such as growth and differentiation of cells, production of EPSs, the collective movement of cells determined by interacting physical forces and chemical cues, e.g., chemotaxis, motility, cellcell signaling, adhesion, and gene regulation (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…EPSs are known to facilitate both colony biofilm expansion (8) and sliding by generating osmotic pressure in the extracellular space (6); however, these previous works are not mentioned.…”
Section: Surfing Of Bacterial Droplets: Bacillus Subtilis Sliding Revmentioning
confidence: 68%
“…An alternative reduced geometry is the lateral expansion of circular biofilms by osmosis (i.e. uptake of fluid into the matrix), for which good quantitative agreement between experiments and continuum modelling is possible [81]. Enhanced models have demonstrated that elastic instabilities can generate wrinkles, even without confinement [10,30] .…”
Section: Fluid-structure Couplingmentioning
confidence: 99%